ANALISA METODE PIECES UNTUK SISTEM PENJUALAN ALAT PROTEKSI RADIASI PADA CV. KASHELARA JAKARTA - Ita Dewi Sintawati; Tri Hartati (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
CV Kashelara is a company engaged in the sale of radiation protection equipment. But it is very unfortunate, the sales system is still manual. This occurs in the recording of customers who buy goods, storing data to making reports. Of course this can cause many errors in recording, inaccurate reports made, and cause time and energy in the process of selling and reporting. This is the reason for researchers to try to analyze the sales system that runs on the company, using the PIECES method. This method is used to analyze whether or not the system is running on the company. The PIECES Framework method consists of: Performance, Information, Economy, Control, Efficiency, and Service. These points are indicators of the feasibility analysis process of the current system. It is expected that in the future with the results of the feasibility test of the current system, researchers can design and even create a system that can overcome the problems of the sales system.